The Association of the Affordable Care Act With Medicaid Enrollment Status and Costs of Care at a Level I Trauma Center in a Medicaid Non-expansion State. Issue 1 (January 2023) - Nahouraii, Michael R.; Cunningham, Kyle W.; Sing, Ronald F.; Sing, Kelly E.; Christmas, Ashley B.
Introduction: The intended purpose of the Patient Protection and Affordable Care Act (ACA) was to expand access to health care insurance for all Americans. In our study, we examine the association of Medicaid enrollment status, health care outcomes, and financial outcomes for trauma patients at a level I urban trauma center in a state that did not expand Medicaid coverage under the ACA. Methods: We retrospectively reviewed trauma admissions from 2011 to 2016, via the trauma registry (n = 36, 250). A subgroup of Medicaid patients (n = 8840) was identified and compared for changes in selected variables and demographics following ACA implementation. The association of Medicaid payor status, by 3 year average pre-ACA (n = 3516) and post-ACA (n = 3324), on patient outcomes, payments collected, and accrued costs of care were analyzed. Results: Three-year Medicaid median actual payments decreased 7.5% following implementation of the ACA (4072 vs. 3767, P < .01). In contrast, the Medicaid median total cost of care increased 23% (3964 vs. 4882, P < .01). The rate of patients insured by Medicaid decreased (24.0% vs. 16.2%, P <.001). Patients were admitted longer (1 d vs. 2 d, P < .01), and more injured (ISS 5 vs. 6, P < .01). Discussion: Medicaid payor status under the ACA was associated with a decrease in actual payments and an increase in total cost of care. Moreover, the divergence in actual payments collected with the increased total cost of care warrants examination to ascertain the root cause in efforts to reduce this widening gap.